Quinolinium Bromochromate as a New Brominating Agent for the Bromination of Metal β-Diketonates - Raman, N.; Paul Pandian, R.; Shunmugasundaram, A. (Asian Journal of Chemistry, 2010)
Reactions of metal(ll) and metal(lII) β-diketones with quinolinium bromochromate (QBC) in glacial acetic acid medium at room temperature produce electrophilic γ-substituted bromo products. The products have been characterised by elemental analyses, IR and 1H NMR spectral studies. Based on the experimental evidences, the reagent QBC can act as a brominating agent for the bromination of metal β-diketonates.